2010
DOI: 10.1155/2010/604615
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Interstitial Fibrosis and Inflammatory Cell Infiltration in Right Ventricles of Systemic Sclerosis-Associated Pulmonary Arterial Hypertension

Abstract: Objective. Systemic sclerosis-associated pulmonary arterial hypertension (SScPAH) has a disturbed function of the right ventricle (RV) when compared to idiopathic PAH (IPAH). Systemic sclerosis may also affect the heart. We hypothesize that RV differences may occur at the level of interstitial inflammation and—fibrosis and compared inflammatory cell infiltrate and fibrosis between the RV of SScPAH, IPAH, and healthy controls. Methods. Paraffin-embedded tissue samples of RV and left ventricle (LV) from SScPAH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 42 publications
1
48
1
Order By: Relevance
“…SSc-PAH patients have more impaired RV function than that observed in IPAH patients despite comparable afterloads 28 ; notably, more inflammatory cells were found in RV tissue samples of the former. 29…”
Section: Inflammation and Autoimmunitymentioning
confidence: 99%
“…SSc-PAH patients have more impaired RV function than that observed in IPAH patients despite comparable afterloads 28 ; notably, more inflammatory cells were found in RV tissue samples of the former. 29…”
Section: Inflammation and Autoimmunitymentioning
confidence: 99%
“…Interestingly, only one single study has reported leukocyte infiltration in the right ventricles obtained from patients with idiopathic PAH (IPAH) and PAH associated with systemic sclerosis (SScPAH) (52). The authors reported a higher number of CD45 ϩ and CD68 ϩ cells in SScPAH compared with RV samples from IPAH patients.…”
Section: Mct-induced Myocarditismentioning
confidence: 99%
“…Macrophages are a prominent component of the inflammatory infiltrates in experimental and clinical PAH 9,35,[71][72][73][74] and are thought to play a very important role in modulating the disease. 9,74 Macrophage depletion or inactivation is shown to prevent experimentally induced hypoxic PH and portopulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%